Edukasi Dampak Stunting Terhadap Pertumbuhan Fisik dan Kognitif Balita Usia 0–2 Tahun di Desa Tanjung Morawa B Kabupaten Deli Serdang Tahun 2025: Pengabdian - Mestika Rija Helti Tanjung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Community Service (PkM) activities in the form of education regarding the impact of stunting on the physical and cognitive growth of toddlers aged 0–2 years were carried out in Tanjung Morawa B Village, Deli Serdang Regency on June 3, 2025. Participants were mothers of toddlers with a total of 20 people. The purpose of the activity was to increase public knowledge and awareness regarding the dangers of stunting and early prevention efforts. The implementation method was in the form of lectures, interactive discussions, and pre-tests and post-tests. The results of the activity showed a 50% increase in participant understanding after being given education. This activity is expected to be able to reduce the risk of stunting through the practice of providing balanced nutrition, exclusive breastfeeding, appropriate complementary feeding, and cognitive stimulation of children.